High-definition ultrasonography for evaluation of embryonic and fetal development in bitch - Maronezi, M. C. [UNESP]; Simões, A. P.R. [UNESP]; Uscategui, R. A.R.; Carneiro, R. K. [UNESP]; Gasser, B. [UNESP]; Silva, P. [UNESP]; Maciel, G. S. [UNESP]; Cruz, I. C.K.; Vicente, W. R. [UNESP]; Feliciano, M. A.R. (FapUNIFESP (SciELO), 2022)
In women, high-definition ultrasonography provides high-quality images of normal and diseased tissues throughout pregnancy, however there are no veterinary studies describing the use of this technology in pregnant dogs. The objective was to evaluate pregnant female dogs daily, using high-definition ultrasonography (HD) in brachycephalic, documenting daily findings of maternal-fetal structures. Twelve healthy brachycephalic females were evaluated daily by HD ultrasound until delivery. It was possible to identify and categorize all maternal, embryonic, and fetal structures and their development, including some fetal tissues not yet described in the literature. The HD exam is an excellent method to monitor the pregnancy of female dogs and identify structures early, providing safe and complete information regarding fetal development
Ultrassonografia de alta-definição para avaliação do desenvolvimento embrionário e fetal em cadelas
Keywords: Canine; Insemination; Organogenesis; Pregnancy; Ultrasonography